AN IMPORTANT FACTOR FOR IMPROVING THE EDUCATIONAL PROCESS ON THE PRINCIPLE OF "LIFELONG LEARNING" - M. M. Akhmedov; S. M. Rozimatova; Z. A. Teshaboev (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the factors of increasing the potential of the science teacher, the level of knowledge of the student, and the efficiency of the educational process, along with the continuous continuation of the "Innovative development" of the subject, which has been enriched with new sources over the years, are described.